2007
DOI: 10.1021/jp076190i
|View full text |Cite
|
Sign up to set email alerts
|

Surface Enhanced Raman Scattering of Carbon Nanotubes Decorated by Individual Fluorescent Gold Particles

Abstract: Confocal optical microscopy was employed to study the effect of surface-enhanced Raman scattering on individual single-walled carbon nanotubes covered with isolated gold particles. The gold particles with diameters between 10 and 120 nm were deposited in low densities on the tubes' sidewalls by an electrochemical method. In the spectra, Raman peaks associated with the nanotubes were found to be superimposed on a broad luminescence background originating from the metal particles. With increasing particle size, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 43 publications
2
40
0
Order By: Relevance
“…The increase in Raman scattering with increase in particle size (as in Figure 3 ) can be mainly attributed to the plasmonic absorption profi le Q ( ω ) of the nanoparticles. [ 36,46 ] This is also confi rmed by obtaining absorption spectra of the G-AuNP hybrids as a function of particle size and density (see Figure S7). Simulations of the extinction cross-section have shown that the plasmonic resonances for gold particles in the size range of 60-120 nm lie around the laser excitation wavelength of 633 nm (see Supporting Information, Figure S6).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The increase in Raman scattering with increase in particle size (as in Figure 3 ) can be mainly attributed to the plasmonic absorption profi le Q ( ω ) of the nanoparticles. [ 36,46 ] This is also confi rmed by obtaining absorption spectra of the G-AuNP hybrids as a function of particle size and density (see Figure S7). Simulations of the extinction cross-section have shown that the plasmonic resonances for gold particles in the size range of 60-120 nm lie around the laser excitation wavelength of 633 nm (see Supporting Information, Figure S6).…”
Section: Resultssupporting
confidence: 57%
“…[ 31 ] The copper foil underneath graphene is etched in a solution of HCl with added H 2 O 2 . [ 36 ] The fl uorescence arises due to recombination of photoexcited carriers at the band edges of the L-and X-points (in reciprocal space) in gold nanostructures and is characteristic of nanoparticles with diameters less than 150 nm. After measuring reference Raman spectra at selected locations, gold nanoparticles are deposited on the surface using electrochemical modifi cation (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…The dark spots represent the gold nanoparticles with particle size in the range of 2 to 7 nm. The X-ray diffractograms of SPANI, f-SWCNT, SPANI/f-SWCNT binary composite (6 wt%) and SPANI/f-SWCNT/Au ternary composite are compared in Figure 3 [20,21]. Further, the ratio of the intensity of these two peaks (I /I ) increases from 0.51 to 0.79 on attaching gold nanoparticles on the SWCNT surfaces indicating an increased disorder and lowering of symmetry as expected.…”
Section: Resultsmentioning
confidence: 54%
“…2 The Raman G band of SWNTs exhibits a significant feature around 1540 cm -1 due to the metallic species. 5,7 The Raman G-band can accordingly be deconvoluted to obtain approximate estimates of the metallic species relative to the semiconducting species (Fig. 3).…”
mentioning
confidence: 99%